2020
DOI: 10.1021/acs.biochem.0c00793
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Validation of a Fourth Guanidine Riboswitch Class in Bacteria

Abstract: An intriguing consequence of ongoing riboswitch discovery efforts is the occasional identification of metabolic or toxicity response pathways for unusual ligands. Recently, we reported the experimental validation of three distinct bacterial riboswitch classes that regulate gene expression in response to the selective binding of a guanidinium ion. These riboswitch classes, called guanidine-I, -II, and -III, regulate numerous genes whose protein products include previously misannotated guanidine exporters and en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…We noted that U17 shows larger changes than G9 and G10 but we cannot explain this. Upon addition of Gdm + (up to 8 mM), the formation of two GC kissing base pairs is reasoned by the detection of two new imino proton signals (Figure 3C 2D spectra ), in line with the base pairs observed in crystal structures [19] . For Gdn23 wt and Gdn49 wt, we see shifts both, for Mg 2+ and additional shift of Gdm + interaction.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We noted that U17 shows larger changes than G9 and G10 but we cannot explain this. Upon addition of Gdm + (up to 8 mM), the formation of two GC kissing base pairs is reasoned by the detection of two new imino proton signals (Figure 3C 2D spectra ), in line with the base pairs observed in crystal structures [19] . For Gdn23 wt and Gdn49 wt, we see shifts both, for Mg 2+ and additional shift of Gdm + interaction.…”
Section: Resultssupporting
confidence: 69%
“…[18] To date, four different classes of Gdm + -sensing riboswitches have been discovered termed guanidine-I to guanidine-IV. [15,18,19] Many of these Gdm + -sensing riboswitches are biologically well characterized and structural models of isolated hairpins were reported for all the four riboswitch classes including Gdn-II from Escherichia coli (PDB: 5NDI), from Gloeobacter violaceus (5NOM and 5NDH) and from Pseudomonas aeruginosa (5VJ9). [14,20] The structures reveal striking similarities of ligand binding pockets between these different riboswitches.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the HRC-8-4 motif vaguely resembles the recently validated HMP-PP [ 17 ] and guanidine-IV [ 21 , 22 ] riboswitch classes. Like these experimentally validated ribo-switch classes, the HRC-8-4 motif generally conforms to the classic architecture of an intrinsic terminator stem [ 64–66 ], which includes a strong stem followed by a run of U nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…HMP-PP and guanidine-IV riboswitches appear to exploit these conserved nucleotides to form the aptamers for their target ligands. This precludes the formation of the terminator stem when ligands bind and thus they function as genetic ‘ON’ switches [ 17 , 21 , 22 ]. We speculate that the HRC-8-4 motif might perform a similar function, although we again cannot be certain that the ligand is a small molecule.…”
Section: Resultsmentioning
confidence: 99%
“…So far, four classes of riboswitches have been identified that bind the cationic molecule guanidinium (Gdm + ): guanidine-I ( Breaker et al, 2017 ), -II ( Sherlock et al, 2017 ), -III ( Sherlock and Breaker 2017 ) and -IV ( Salvail et al, 2020 ). The corresponding genes are in most cases involved in Gdm + detoxification, and code for proteins like guanidine carboxylases or multidrug efflux pumps (e. g., SugE).…”
Section: Introductionmentioning
confidence: 99%